UJI FASTENING PADA KAYU KOMPOSIT SERAT PANDAN WANGI DAN LIMBAH KAYU DENGAN RESIN POLYESTER - Sulistyowati, Emmy Dyah; Sari, Nasmi Herlina; Sinarep, S.; Pandiatmi, Pandri; Andrian, Insan (Universitas Mataram, 2015)
The purpose of this study was to obtain handling connection type in use as door panels, roofing sheets, walls and floors. Therefore, the tests performed are fastening test and abrasion test. The technique of making wood composite is using hand lay-up technique. Constituent material of board composite is using pandanwangifibers with length variationsare 15 mm, 20 mm, and 30 mm with volume fraction variations are 20% and 30%, and 5% Sengon tree saw-dust is used as the filler. The results showed that pre-drilling with fastener sizes # 6, # 8 and # 10 is 3.5 mm, 4 mm and 4,5mm. The distance between each fastener depends on the fastener head itself, ie fastener # 6, # 8, and # 10. Critical distance between the edge of the fastener has a significant effect on fiber length and volume fraction. The highest value is shown on 15 mm of the fiber length and 20% of volume fraction with the value 3.29 mm, and the lowest value is shown on 15 mm of the fiber length and 30% of volume fraction with the value 2.74 mm.